Deformation stimulated precipitation of a single-phase CoCrFeMnNi high entropy alloy. (June 2017) - Zhou, W.; Fu, L.M.; Liu, P.; Xu, X.D.; Chen, B.; Zhu, G.Z.; Wang, X.D.; Shan, A.D.; Chen, M.W.
Abstract: We report transmission electron microscope characterization of phase decomposition in a single-phase CoCrFeMnNi high entropy alloy (HEA) subjected to cold rolling and subsequent annealing at intermediate temperatures. It is found that plastic deformation plays a key role in phase destabilization of the HEA during intermediate annealing. The formation of Cr-rich precipitates in recrystallized grains and recovered samples suggests that dislocations generated by cold rolling is one of the critical factor leading to the destabilization of the stable HEA. Atomic-scale characterization of the Cr-rich precipitates reveals a complex crystallographic structure which is comprised of one-dimensional pentagons with selective atomic occupation. This study indicates that the phase stability of HEAs is very fragile at intermediate temperatures at which the multicomponent solid solutions stabilized by high configurational entropy may break down by local chemical disturbance at dislocations and grain boundaries. Graphical abstract: Highlights: The mechanism of deformation induced phase destabilization of HEAs is revealed. Dislocations are the critical factor leading to the destabilization of the stable HEA. Cr-rich precipitates have a complex crystallographic structure comprised of one-dimensional pentagons with selective atomic occupation.